Loeffler's Endocarditis and Hypereosinophilic Syndrome. Issue 3 (May 2021) - Salih, Mohammed; Ibrahim, Ramzi; Tirunagiri, Deepthi; Al-ani, Hadeel; Ananthasubramaniam, Karthik
Abstract : Loeffler's endocarditis and hypereosinophilic syndromes are a unique group of infiltrative disorders characterized by hypereosinophilia, inflammatory thrombotic, and ultimately, fibrotic involvement of the heart leading to multiple complications including valve involvement, thromboembolic phenomena, heart failure. Clinical recognition, comprehensive laboratory and multimodality imaging diagnostic workup, and early initiation of treatment have been shown to slow down the progression and promote remission. This review addresses a detailed analysis of Loeffler's endocarditis and hypereosinophilic syndromes.